2008
DOI: 10.1248/cpb.56.930
|View full text |Cite
|
Sign up to set email alerts
|

Briaexcavatins M-P, Four New Briarane-Related Diterpenoids from Cultured Octocoral Briareum excavatum (Briareidae)

Abstract: Gorgonian corals are recognized as rich sources of diterpenoid derivatives with the well-known briarane carbon skeleton, a group of diterpenoids having a highly oxidized bicyclo [8.4.0] system with a g-lactone group. Compounds of this type exist only in marine organisms, particularly in octocorals.1,2) In our screening for novel natural products from the marine invertebrates collected in Taiwanese waters, we have discovered a series of terpenoid and steroid metabolites from the octocorals Alcyonium sp., 3,4) B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The Z-configuration of C-5/C-6 double bond was elucidated by a correlation between H-6 and H 3 -16. The NMR data of 2 were found to be similar to those of a known briarane, briaexcavatin P (5) [9]. It was found that the 2-acetoxy substituent in 5 was replaced by a hydroxy group in 2.…”
Section: Inosmentioning
confidence: 72%
See 1 more Smart Citation
“…The Z-configuration of C-5/C-6 double bond was elucidated by a correlation between H-6 and H 3 -16. The NMR data of 2 were found to be similar to those of a known briarane, briaexcavatin P (5) [9]. It was found that the 2-acetoxy substituent in 5 was replaced by a hydroxy group in 2.…”
Section: Inosmentioning
confidence: 72%
“…The compounds of this type are only found in marine invertebrates, particularly in octocorals and demonstrated a wide spectrum of bioactivities, such as anti-inflammatory activity [6] and cytotoxicity [7]. In our continuing research into the chemical constituents of an octocoral B. excavatum (Nutting 1911), which was distributed extensively in the coral reefs of Taiwan, have resulted in isolation of three previously unreported 8,17-epoxybriaranes-briarenols I-K (1-3) along with two known analogues, briaexcavatolide P (4) [8] and briaexcavatin P (5) [9],…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, based on the above findings, the s-trans diene moiety in 1 was elucidated. The NMR data of 1 were found to be similar to those of briarane derivatives with a 3E,5Z-diene system, such as briaexcavatin M [9], briaranolides I and J [10], excavatolide F [11] and briarenolide ZII (2) ( Figure 1) [12]. Thus, briarane 1 was identified as the 12-O-debutyryl derivative of 2.…”
mentioning
confidence: 72%
“…The compounds of this type were suggested to be of marine origin and the octocorals belonging to the genus Briareum have been proven to be the most important source of briarane-type compounds [4,5,6,7]. In previous studies, a series of interesting terpenoid derivatives, including briarane [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35], cembrane [36] and carotenoid [37], had been isolated from the octocorals belonging to the genus Briareum that were distributed in the waters off Taiwan, at the intersection point of the Kuroshio current and the South China Sea surface current. In a continuation of our search for new substances from the Formosan marine invertebrates, the chemical constituents of a specimen octocoral identified as Briareum sp.…”
Section: Introductionmentioning
confidence: 99%